Cricket-based robots. - Birch, M.C (IEEE Robotics and automation magazine)
This article describes the development of an autonomous hybrid microrobot that uses legs for propulsion and support of the rear half of the body and a pair of wheels for support of the front half. McKibben artificial muscles actuate the legs, and compressed air is generated by an onboard power plant. Control is also onboard in the form of a PIC microcontroller, from Microchip Technology Inc., that controls the actuators through four three-way valves that are each made up of a pair of microelectromechanical system devices. Its motion resembles that of a cricket.